Assessment of intra-fraction motion during automated linac-based SRS treatment delivery with an open face mask system. (December 2021) - De Ornelas, Mariluz; Diwanji, Tejan; Monterroso, Irene; Bossart, Elizabeth; Yechieli, Raphael; Dogan, Nesrin; Mellon, Eric A.
Highlights: Intra-fraction motion assessment utilizing Varian HyperArc with Encompass masking system along with real-time surface tracking. Margin required for single-isocenter linac-based radiosurgery for single and multiple targets. Rotational effect on targets at a distance from isocenter. Maximum isocenter-to-target distance to maintain target coverage. Abstract: Purpose/objective: To evaluate intra-fraction target shift during automated mono-isocentric linac-based stereotactic radiosurgery with open-face mask system and optical real-time tracking. Materials/methods: Ninety-five patients were treated using automated linac-based stereotactic radiosurgery in 1–5 fractions with single isocenter for a total of 195 fractions. During treatment, patient positioning was tracked real-time with optical surface guidance and immobilized with a rigid open-face mask. Patients were re-positioned if optical surface guidance error exceeded 1 mm magnitude or 1°. Translational and rotational intra-fractional changes were determined by post-treatment CBCT matched to the planning CT. Target specific error was calculated by translation and rotation matrices applied to isocenter and target spatial coordinates. Results: For 132 fractions with isocenter within a single target, the median shift magnitude was 0.40 mm with a maximum shift of 1.17 mm. A total of 398 targets treated for plans having multiple or single targets that lied outside isocenter, resulted in a median shift magnitude of 0.46 mm, with median translational shifts of 0.20 mm and 0.20° rotational shifts. A 1 mm PTV margin was insufficient in 18% of targets at a distance greater than 6 cm away from isocenter, but sufficient for 96% of targets within 6 cm. Conclusions: The findings of this study support 1 mm PTV expansion due to intra-fraction motion to ensure target coverage for plans with isocenter placement less than 6 cm away from the targets.